Approaching the labor market from a generational perspective. (August 2019) - Pop, D; Pop, M T
Abstract: Generation research has grown even broader and has deeply extended in the last 30 years. It can be said that the use of research results related to generations in the human resources management is a certainty in to use the best recruitment, selection, and integration methods of employees, to implement the best methods and techniques of stimulating the employee's creativity and innovation in organizations, communication, etc. An important phenomenon emerged as a result of the generational conflict, which has been highlighted in recent years, is that of the young people named "idlers", i.e., those inactive on the labor market, called NEET.